Klasyfikacja w wyborze nieruchomości podobnych na potrzeby wyceny rynkowej nieruchomości - Pawlukowicz, Roman (Classification in the Selection of Comparable Properties for the Appraisal of Property Market Value, 2006)
The determination of market value, which is an element of property appraisal, requires not only information on the property but also on comparable properties. The existing methodology of appraisal in Poland, which regards this requirement as a matter of utmost importance, does not by any means determine the way to define a set of comparable properties. In doing so. it leaves room for the appraisers' intuition. Frequently, the consequence of this is a discrepancy in the final results of the appraisal of the same property as obtained by independent appraisers. The article considers possibilities of the objectification of the comparable properties selection by utilizing the formal process of multidimensional classification. Specifically discussed are the problems involving the decision of the appraiser in regard to the choice of correct procedure for their resolution.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (16); 2006; nr 1100, s. 232-240